INSTITUSIONALISASI SISTEM INA-CBGs (Indonesia-Case Based Groups), STRATEGI EFEKTIVITAS DAN EFISIENSI ORGANISASI: STUDI KASUS PADA RUMAH SAKIT UMUM DAERAH Dr. SAIFUL ANWAR - CITRUS CLARIAS ; Eko Ganis Sukoharsono,Aji Dedi Mulawarman
This interpretive case study is used to find about institutionalization INACBGs_x000D_ _x000D_ system also effectiveness and efficiency strategy in Regional Public_x000D_ Hospital Dr. Safiul Anwar Malang (RSSA). Since 2014 the government has_x000D_ introduced INA-CBGs system as a method of payment claims on advanced_x000D_ health facilities. Institutional theory introduced by Dimaggio and Powell (1991) is_x000D_ used to understand how the INA-CBGs system has been institutionalized in_x000D_ RSSA with technically and policies._x000D_ The study found that implementation of INA-CBGs system quickly in a_x000D_ relatively short period of time only succeeded in institutionalizing new system_x000D_ through agreement and compromise. Institutionalization of INA-CBGs system in_x000D_ RSSA more towards enhancement legitimacy as public hospitals. However,_x000D_ increase in revenue and the number of patients JKN, appears to be a significant_x000D_ factor for instituting new system in their service strategy rather than for improving_x000D_ quality of care and cost efficiency. Management effectiveness and efficiency_x000D_ strategy not optimal make INA-CBGs system has been unable to make the_x000D_ hospital to be effective and efficient in serving patients. At the end, INA-CBGs_x000D_ system became a tool for the public hospitals in fulfilling revenue targets of local_x000D_ government and central government also reduce serving for patients._x000D_ _x000D_ Keywords: Institutionalization, INA-CBGs Systems, Organizational Effectiveness _x000D_ and Efficiency Strategy